Bed expansion characteristics in sound assisted fluidization of Geldart's group A powder - Parimanan Cherntongchai (2018)
© 2018 Elsevier B.V. Intrinsic bed expansion characteristics in a sound assisted fluidization of Geldart's group A powder were investigated. To obtain an accurate bed expansion data, a 1-valve and 2-valve bed collapse experiment, together with a bed collapse model for a correct interpretation of bed collapse curves, was used. It was found that a total bed voidage and a dense phase for the sound assisted fluidization were varied with an inlet superficial velocity in the same fashion as those for a conventional fluidization. Besides, the voidage with respect to the inlet superficial velocity of the sound assisted fluidization was found to be lower, in comparison with those of the conventional fluidization and was independent on a sound frequency. On the other hand, dense phase voidage and its superficial velocity relations of the sound assisted fluidization at the different sound frequencies were approximately on the same trend as that for the conventional fluidization. And, a minimum bubbling point, defined using the dense phase voidage and the dense phase superficial velocity characteristic curve, was also unaffected by the sound vibration force. These findings suggested that the sound vibrational force tended to create more cavity or bubble phase in the fluidized bed, rather than changing a hydrodynamics relation in the dense phase. Therefore, the same equilibrium of force as that of the conventional fluidization can still be applied for the sound assisted fluidization, as well as stability criteria. Finally, it was proved that the modified revised Ergun drag force correlation, applicable for the conventional fluidization, can describe well the dense phase voidage and the dense phase superficial velocity characteristic curves of the sound assisted fluidization. Likewise, the stability criterion, proposed by Cherntongchai and Brandani in 2013, can predict excellently the minimum bubbling points for the sound assisted fluidized bed.